“I Must Try Harder”: Design Implications for Mobile Apps and Wearables Contributing to Self-Efficacy of Patients With Chronic Conditions - Wulfovich, Sharon; Fiordelli, Maddalena; Rivas, Homero; Concepcion, Waldo; Wac, Katarzyna (Frontiers in Psychology, 2019)
Background: Diverse wellness-promoting mobile health technologies, including mobile apps and wearable trackers, became increasingly popular due to their ability to support patients' self-management of health conditions. However, the patient’s acceptance and use depend on the perceived experience and the app appropriateness to the patient’s context and needs. We have some understating of the experience and factors influencing the use of these technologies in the general public, but we have a limited understanding of these issues in patients. Objective: By presenting results from an explorative study, this paper aims to identify implications for the design of mobile apps and wearables to effectively support patients' efforts in self-management of health with a special emphasis on support for self-efficacy of activities contributing to health. Methods: An explorative mixed-method study involving 200 chronically ill patients of Stanford Medical Center (Stanford, USA, CA) was conducted between mid-2016 and end of 2018. Amongst these, 20 patients were involved in a 4-weeks study, in which we collected the underlying wearable device use logs (e.g., Fitbit) and subjective use experience (via an Ecological Momentary Assessment), as well as patients’ momentary perception of general self-efficacy in their natural environments and different daily contexts. Results: The results indicate that mobile apps for health and wearables have the potential to enable better self-management and improve patients’ wellbeing but must be further refined to address different human aspects of their use. Specifically, the apps/wearables should be easier to use, more personalized and context-aware for the patient’s overall routine and lifestyle choices, as well as with respect to the momentary patient state (e.g., location, type of people around) and health(care) needs. Additionally, apps and devices should be more battery efficient and accurate; providing timely, non-judgmental feedback and personalized advice to the patients anywhere-anytime-anyhow. These results are mapped on major sources of the individuals’ self-efficacy. Conclusion: Our results show how the apps/wearables that are aimed at supporting the patients’ self-management should be designed to leverage and further improve the patients’ general self-efficacy and self-efficacy of activities contributing to chronic disease management.